Säga nej: Nedslag i olydnadens litteraturhistoria - Olsson, Ulf (K&K - Kultur og Klasse, 2023)
In 2011, during the occupation of Zucotti Park in New York, Occupy Wall Street arranged a public reading of Herman Melville’s novella Bartleby, 1853. The widely discussed choice of this story points to OWS’s own politics: the movement said ”no”, but without forming any more specific demands for reform. This article, taking its theoretical lead from Judith Butler, Marcello Tarì and Michel Foucault, discusses if the self can be re-modelled. Bartleby and his refusal – “I would prefer not to” – is related to one other prominent no-sayer in literature: Stiller. Refusal is also the theme of Max Frisch’s novel Stiller, 1954, in which the protagonist simply refuses to acknowledge the identity that everyone, authorities as well as his wife, forces upon him. That way, he also refuses the society in which he lives, and its political subject in the form of the citizen. Stiller thereby illustrates Foucault’s theses that we must refuse who we are. Bartleby and Stiller can both be understood as examples of the obstinacy that Alexander Kluge and Oskar Negt have emphasized as the basic form of resistance.